9/11 Twenty Years On: Fractured Identities; Fear of the Other; Forging a New Path for Our Children Introduction to the Section. Issue 1 (31st December 2022) - Lament, Claudia; Ismi, Naghma Mimi
ABSTRACT: This is an introduction to a collection of papers that commemorates the twentieth anniversary of 9/11. The nature of the content of the papers which follow is spurred by reflections on this anniversary from a number of domains: child and adult psychoanalysis; the healing arts of theater; the parent-child treatment of Afghani and Iraqi asylum-seeking families; the Law of the Mother and siblingships; the changes occurring in psychoanalytic views of secularism; and the confrontation of racial prejudice and othering in the workplace and its repercussions upon the self. Concepts of splitting, the bearing of ambivalence, and the capacity to reflect and resist fragmentation are illuminated.